The Effect of Dividends on Future Earnings - Endah Puji Lestari; Kusharyanti; Noto Pamungkas; Sri Hastuti (www.amertainstitute.com, 2025)
This study aims to analyze the effect of dividends on future earnings. This research uses a quantitative approach with comparative and causal methods. Secondary data is processed from the financial statements of energy companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The results of research on energy companies in Indonesia during the observation period, as well as testing and estimation using the Common Effect Model (CEM), can be concluded that dividend is positive and does not have a significant effect on future profits. Then for the control variable, profit, has an effect on future profits and the accrual variable has no effect on future profits. This indicates that dividends have a less strong effect on future earnings. Companies continue to distribute and adjust dividends, so dividends are seen more as a corporate governance mechanism than a direct signal regarding future earnings. In situations where information is highly limited and uncertain, corporate actions such as upward or downward dividend adjustments in response to current conditions can hopefully be considered as information signals.